Developing a decision support tool for the continuation or deprescribing of antithrombotic therapy in patients receiving end-of-life care: Protocol for a European Delphi study - Imene Deneche; Camille Couffignal; Nassima Si Mohammed; Anette Arbjerg Højen; Carme Font; Stavros Konstantinides; Marieke Kruip; Luigi Maiorana; Sebastian Szmit; Denise Abbel; Laurent Bertoletti; Susanne Cannegieter; et al. (Thrombosis Update)
Introduction: To develop a European shared decision support tool (SDST), a Delphi process will be used to reach consensus about aspects relating to the continuation or deprescribing of antithrombotic therapy (ATT) in cancer patients at the end of life. As part of the SERENITY project, this study corresponds to work package (WP) 4. Methods: Findings from SERENITY WPs 1–3 (realist review, flash mob research, epidemiological and qualitative studies) informed the Delphi study. The WP4 steering committee had two objectives. (1) to build a representative expert panel comprising physicians, pharmacists, nurses and psychologists from eight European countries; and (2) to advise on the content of the Delphi form, divided into four sections: context, content, SDST design and trial outcomes. The form was reviewed by the SERENITY patient and public involvement group to ensure that it met patients’ needs. The Delphi study will take place in three rounds held at 6-week intervals, involving experts from eight countries. Consensus will be reached on items with at least 70 % agreement. The steering committee will review and validate the results across the different rounds. Results: Through this Delphi study, the following aspects will be defined: characterisation of candidate patients for discussion about ATT deprescribing; healthcare team roles in ATT decision-making; specific information and communication requirements for patients when making deprescribing decisions; SDST content priorities; and optimal outcomes for the planned clinical trial. Conclusion: This study will feed directly into the development and evaluation of the SDST, aimed at reducing complications and improving quality-of-life in end-of-life cancer patients receiving ATT.